2012
DOI: 10.1371/journal.pone.0042124
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymorphisms and Biocontrol of Bacillus Antagonistic to Citrus Bacterial Canker with Indication of the Interference of Phyllosphere Biofilms

Abstract: Citrus bacterial canker caused by Xanthomonas axonopodis pv. citri is a devastating disease resulting in significant crop losses in various citrus cultivars worldwide. A biocontrol agent has not been recommended for this disease. To explore the potential of bacilli native to Taiwan to control this disease, Bacillus species with a broad spectrum of antagonistic activity against various phytopathogens were isolated from plant potting mixes, organic compost and the rhizosphere soil. Seven strains TKS1-1, OF3-16, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
0
26
0
2
Order By: Relevance
“…6). Reductions in citrus canker severity and incidence were also reported for citrus species treated with the Bacillus strains WG6-14 and TKS1-1 and with B. subtilis (S-12) (Das et al, 2014; Huang et al, 2012). B. subtilis , B. amyloliquefaciens , B. pumilus , B. mycoides , B. pasteurii , and B. cereus induce plant disease resistance and are commercially available as biocontrol agents (Kloepper et al, 2004; Nam et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…6). Reductions in citrus canker severity and incidence were also reported for citrus species treated with the Bacillus strains WG6-14 and TKS1-1 and with B. subtilis (S-12) (Das et al, 2014; Huang et al, 2012). B. subtilis , B. amyloliquefaciens , B. pumilus , B. mycoides , B. pasteurii , and B. cereus induce plant disease resistance and are commercially available as biocontrol agents (Kloepper et al, 2004; Nam et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…Our previous study indicated that Bacillus subtilis TKS1-1 and Bacillus amyloliquefaciens WG6-14 can interfere with phyllosphere biofilm formation by X. axonopodis pv. citri , which may contribute to the attenuation of citrus bacterial canker symptom development [6]. These results and findings from other plant-associated bacteria suggest that biofilm formation plays important roles in pathogenesis [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 67%
“…citri , which may contribute to the attenuation of citrus bacterial canker symptom development [6]. These results and findings from other plant-associated bacteria suggest that biofilm formation plays important roles in pathogenesis [5], [6], [7], [8]. Thus, experiments were conducted to uncover genes and gene clusters that are involved in biofilm formation and virulence as well as to reveal potential interactions between these two processes in X. axonopodis pv.…”
Section: Introductionmentioning
confidence: 99%
“…antimicrobial compounds) manner [54], [77], [78]. For example, it has been shown that pre-inoculation of Citrus and tomato plants with plant growth promoting and biocontrol bacteria like Azospirillum brasiliense or Bacillus strains, which themselves have no negative effects on the plants, prevents the development of large populations of pathogenic bacteria [79], [80]. For Arabidopsis , antagonistic effects of specifically plant-associated Sphingomonas strains to a plant-pathogenic Pseudomonas syringae strain were described [81].…”
Section: Discussionmentioning
confidence: 99%